Obtaining Ultra-long Wear Lifetime of Graphene Oxide Films Under High Contact Stress Through Soft and Hard Interbeded Formation Mode - Chen, Li; Zhu, Hang; Wu, Gang; Mu, Bo; Liu, Yaqian; Zhang, Xingkai; Bai, Changning (Tribology letters, 2025)
As the quintessential representation of graphene derivatives, graphene oxide (GO) has demonstrated unparalleled potential in micro/nano electronic mechanical systems, which visibly enhances the efficiency and accuracy of moving mechanical devices. However, GO has always been subject to the problem of insufficient wear lifetime, and the subsequent improvement is still a challenge, especially under high contact stress. In this paper, making use of the strong charge interactions between positively charged poly(acrylamide-co-diallyldimethylammonium chloride) (Brand: PQ-7) and negatively charged GO, both were alternately spin-coated on the silicon substrates modified by 3-aminopropyltriethoxysilane as an adhesive layer to form (GO/PQ-7) n composite multilayer film. The service life of (GO/PQ-7) 5 multilayer film exceeds 27000 s under high load of 4N, which is 20 times longer than that of the GO film. The superior friction performance is ascribed to the distinctive structure of (GO/PQ-7) n composite multilayers, that is, an elastic 3-dimensional stack composed of rigid GO and flexible polymer. This soft and hard interbeded formation film not only integrates the interface well, but also effectively prevents the crack expansion. It also leverages the advantages of soft layers providing stress relief and hard layers providing load-bearing capacity. What's more, friction-induced conversion of partial GO to graphene ensures low friction at the sliding interface. This strategy provides an open platform for the design and fabrication of lubricating films for micro/nano electronic mechanical systems and other microdevices.